Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae) - Wu, Shipher; Chang, Wei-Chun (Zootaxa, 2018)
The present study re-assesses the characters of the Oriental genus Lobogonodes Bastelberger, 1909 based on all 8 species, including the newly described L. shiushioui sp. nov. and the distinct species L. dactylotypa Prout, 1940 stat. rev.. Three synapomorphic characters based on the male genitalia are proposed: the presence of a sclerotized subscaphium, the U-shaped connection between the juxta and anellus lobe and the saccus process pointed anteriorly. A new key to the species in this genus is provided.